Can Households Cope with Health Shocks in Vietnam?. (28th May 2015) - Mitra, Sophie; Palmer, Michael; Mont, Daniel; Groce, Nora
Abstract: This paper investigates the economic impact of health shocks on working‐age adults in Vietnam during 2004–2008, using a fixed effects specification. Health shocks cover disability and morbidity and are measured by 'days unable to carry out regular activity', 'days in bed due to illness/injury', and 'hospitalization'. Overall, Vietnamese households are able to smooth total non‐health expenditures in the short run in the face of a significant rise in out‐of‐pocket health expenditures. However, this is accomplished through vulnerability‐enhancing mechanisms, especially in rural areas, including increased loans and asset sales and decreased education expenditures. Female‐headed and rural households are found to be the least able to protect consumption. Results highlight the need to extend and deepen social protection and universal health coverage. © 2015 The Authors. Health Economics published by John Wiley & Sons Ltd.